DYNAMIC CAPABILITIES AND B2B BRANDING IN INDUSTRIAL MARKETS - German, Ana Maria; Nechita, Florin (My University, 2015)
Nowadays, change is an inevitable factor in the development of any organization. The dynamic business environment has brought new challenges for organisations, industries and countries. Success in such times demands new perspectives on competitiveness and performance. In the context of business performance, the focus should be on the dynamic capabilities and on brand strategies that contribute to the development of the organisations. In this paper we analyze the industrial B2B branding as a posible source of obtaining competitive advantage and business performance.
Keywords: dynamic capabilities; B2B organisations; brand equity; performance; industrial markets